Robert Burns and Religion - McGinty, Walter (Taylor and Francis, 2018)
Cover -- Half Title -- Dedication -- Title Page -- Copyright Page -- Table of Contents -- Acknowledgements -- 1 âThe Cultivation of the Finer Feelings of the Heartâ -- 2 âA Proven Fornicatorâ -- 3 âStill I am a Very Sincere Believer in the Bibleâ -- 4 âThough Sceptical on Some Points of our Current Beliefâ -- 5 âIf There be a Life Beyond the Graveâ -- 6 âI am an Accountable Creatureâ -- 7 William Cowper -- 8 Christopher Smart -- 9 The Ministers of âThe Kirk of Scotlandâs Garland - a New Songâ -- 10 Poems Reflecting the Recurrent Themes of a Benevolent God, Life After Death and Accountability -- Epilogue -- Appendix Reverend William McGill -- References and Notes -- Bibliography -- Index